Bioethics training programmes for Africa: evaluating professional and bioethics-related achievements of African trainees after a decade of Fogarty NIH investment - Kass, Nancy E (BMJ Open, 2016)
OBJECTIVES: Our primary aim was to evaluate the impact of US National Institutes of Health (NIH)-funded bioethics training programmes (Fogarty bioethics training programmes, FBTPs) that trained individuals from Africa over the programme's first 10 years to examine changes between pretraining and post-training in individual achievement and to document any associations between individual, training programme and post-training accomplishments. DESIGN: We surveyed trainees from the 10 bioethics programmes funded by NIH Fogarty International Center from 2000 to 2011 that included African trainees. McNemar's and Wilcoxon signed rank-sum tests were used to analyse pre–post levels of general and bioethics-related professional achievement. Likelihood of specific post-training achievement outcomes was measured using logistic regression including demographic, pretraining and intratraining variables. SETTING: 10 different FBTPs that trained individuals from Africa from 2000 to 2011. PARTICIPANTS: Of 253 eligible respondents, 171 completed the survey (response rate 67.6%). PRIMARY OUTCOME MEASURES: Pre–post comparisons of professional achievement indicators (eg, serving in leadership roles, teaching, publishing manuscripts); likelihood of specific post-training achievement outcomes. RESULTS: Post-training, respondents were significantly more likely to report serving in a leadership role, being an investigator on a research grant, serving on international committees, serving as a mentor, and publishing manuscripts than at pretraining. Post-training, significantly greater numbers of respondents reported bioethics-related achievements including being a bioethics instructor, serving on an Institutional Review Board (IRB), being an investigator on a bioethics grant and publishing bioethics-related manuscripts than pretraining. Controlling for other factors, there were no significant differences by gender in the post-training success of these participants in terms of leadership roles, being instructors, investigators on grants and holding IRB roles. CONCLUSIONS: African trainees who participated in FBTPs reported significantly higher levels of professional achievement after training. There was no single factor—either demographic, related to a trainee's professional background, or in programme design—that consistently predicted greater levels of post-training achievement.